Paediatric bed capacity in Swiss hospitals: a comprehensive analysis (Swiss Medical Weekly, 2025)
BACKGROUND: Switzerland’s decentralised healthcare system delegates responsibility for paediatric hospital infrastructure to individual cantons. To date, official statistics on the number and types of paediatric hospital beds are lacking.OBJECTIVE: This study sought to fill this gap by collecting and analysing data from all paediatric hospitals in Switzerland.METHODS: A nationwide cross-sectional e-mail survey was conducted in January 2023. Data on both structurally available and operated beds were collected and descriptively analysed.RESULTS: The survey identified a total of 1751 beds in 29 paediatric hospitals or departments, of which 85% were operated. Of the total beds, 112 were paediatric intensive care unit beds (80% operated) and 339 were neonatology beds (86% operated). Significant regional disparities in bed availability were identified: the Lake Geneva region has the highest bed-to-child ratios, while Central Switzerland, Eastern Switzerland and Ticino show notably lower ratios.CONCLUSION: These findings highlight the current distribution of paediatric beds, the considerable proportion of non-operated beds, and the importance of continued, comprehensive data collection to inform healthcare planning.